Selective targeting of c-Abl via a cryptic mitochondrial targeting signal activated by cellular redox status in leukemic and breast cancer cells - Constance, Jonathan E. (2012)
PURPOSE: The tyrosine kinase c-Abl localizes to the mitochondria under cell stress conditions and promotes apoptosis. However, c-Abl has not been directly targeted to the mitochondria. Fusing c-Abl to a mitochondrial translocation signal (MTS) that is activated by reactive oxygen species (ROS) will selectively target the mitochondria of cancer cells exhibiting an elevated ROS phenotype. Mitochondrially targeted c-Abl will thereby induce malignant cell death. METHODS: Confocal microscopy was used to determine mitochondrial colocalization of ectopically expressed c-Abl-EGFP/cMTS fusion across three cell lines (K562, Cos-7, and 1471.1) with varying levels of basal (and pharmacologically modulated) ROS. ROS were quantified by indicator dye assay. The functional consequences of mitochondrial c-Abl were assessed by DNA accessibility to 7-AAD using flow cytometry. RESULTS: The cMTS and cMTS/c-Abl fusions colocalized to the mitochondria in leukemic (K562) and breast (1471.1) cancer phenotypes (but not Cos-7 fibroblasts) in a ROS and PKC dependent manner. CONCLUSIONS: We confirm and extend oxidative stress activated translocation of the cMTS by demonstrating that the cMTS and Abl/cMTS fusion selectively target the mitochondria of K562 leukemia and mammary adenocarcinoma 1471.1 cells. c-Abl induced K562 leukemia cell death when targeted to the matrix but not the outer membrane of the mitochondria.